Zmanjševanje emisij dušikovih oksidov z rekonstrukcijo zgorevalnega sistema kotlov v Termoelektrarni toplarni Ljubljana - Oman, Janez (Strojniški vestnik, 2005)
In Slovenia, NOx emissions from boilers of 50 to 500 MW must be under 650 mg/m3 by the end of year 2007. Afterwards, the limit will be 600 mg/m3. The emissions of the Power Plant Ljubljana have often exceeded the stated limiting values. After the reconstruction of the firing system of boiler 3, which was carried out using knowledge from abroad, it was necessary to reconstruct the firing systems of boilers 1 and 2, which remained the main sources of NOx and CO emissions. The reconstruction based on domestic knowledge was carried out by experts from the Power Plant Ljubljana and the Faculty of Mechanical Engineering, Ljubljana. The paper describes the essence of the reconstruction and its results. Besides lower emissions there was also a significant improvement in the efficiencies of the boilers.
Keywords: emisije NOx; sistemi zgorevalni; učinkovitost zgorevanja; gorilniki; izpušni plini; dušikovi oksidi; termoelektrarne; zgorevalne naprave